Reactive mesothelial proliferation: a necropsy study. Issue 12 (December 1981) - Sheldon, C D; Herbert, A; Gallagher, P J
Abstract : To establish a histological standard against which surgical biopsy material could be compared, the degree of mesothelial proliferation was studied in 100 unselected necropsies. A minor degree of mesothelial hyperplasia was identified in 10 cases, usually close to areas of fibrous adhesions. Pleural plaques were present in 33 patients but there was no evidence of associated mesothelial proliferation. No mesothelial changes were noted in patients with empyema or pleural metastases. These findings indicated that the degree of mesothelial hyperplasia in common disorders of the pleura is relatively slight. Significant mesothelial proliferation in needle biopsies should therefore be viewed with considerable suspicion and, where clinically appropriate, be followed by further investigation.